PERISTILAHAN PERALATAN TRADISIONAL DALAM AKTIVITAS MASYARAKAT DAYAK KETUNGAU SESAT DI DUSUN GONIS BUTUN - Damayanti, Sisilia Yunita; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the traditional terminology tools in the activities of the Dayak Ketungau Sesat community in Sekadau District to develop community culture with a documentation. The research was used descripfive method with qualitative models. The data sources of this study involved six informant that of research used as a data source to obtain data related of the traditional equipment. Data engineering techniques, using 'converse' techniques, advanced proficiency techniques, recording techniques, and note-taking techniques. Tool of used in this researcher himself as a key instrument assisted with a recording device and notebooks. The results of this study was seventy product of traditional equipment terminology data consisting of six activities, namely cooking activities with the number of twelve terminology data, activities of rice farming of twenty-three terminology data, activities of capturing fish data with nine terminology data findings. Activities to hunt six terminology data, carpentry activities was found eighteen terminology data, and the last of ceremony activity two data terms. The six activities of the researcher was limited to materials made of metal, clay, wood, stone, rattan, and spiny pandan leaves. This research also produces description texts, procedure texts, and exposition texts that can be used as a supplement for Indonesia language teaching materials at the community of Dayak Ketungau Sesat community in Sekadau District. Keywords: terminology, tool, activities, traditional, Dayak Ketungau Sesat